Synthesis and Characterization of Some Novel Biphenyl-4- carboxylic Acid (4-Benzylidene-5-oxo-2-subsituted phenyl-4,5-dihydro-imidazol-1-yl)amide - V. Patel, Anil; Malik, G.M. (Asian Journal of Chemistry, 2010)
Imidazolinone derivatives of 4a-h have been prepared by the condensation of biphenyl-4-carboxylic acid hydrazide (2) with 5-oxazolone derivatives, which were prepared by Erlenmeyer condensation of benzoyl glycine with different aldehydes in presence of sodium acetate and acetic anhydride. The compounds 3a-h was further reacted with biphenyl-4- carboxylic acid hydrazide (2) to give 4a-h in basic condition. The constitution of the products has been supported by IR, 1H NMR, 13C NMR mass spectra and elemental analysis data.